THE EFFECT OF ORIENTALISM: THE CHALLENGE OF DA'WAH FOR ISLAMIC UNIVERSITY IN INDONESIA - Lukman Lukman (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2022)
The purpose of this study is to reveal the influence and dangers of orientalism at Islamic universities in Indonesia. Research method with qualitative approach. The research results or findings from this study are many Islamic universities in Indonesia have been infected and influenced by Orientalist understanding in understanding religion. Orientalist methodologies and scholarship have been widely used and taught in Islamic campuses without any criticism and adjustment to Islamic teachings. So that it has an impact on the understanding and perspective of students and lecturers on Islamic campuses, there are those who then think that all religions are true, it is permissible to marry between different religions, you can't be panicky about religion, question the authenticity of the Qur'an and other understandings of relativism. Of course, these kinds of ideas deviate from the teachings of Islam which is perfect from all sides. Then it becomes a challenge and obligation for Islamic universities to refer back to important concepts in every Islamic discipline and apply it in the context of contemporary sciences in response to 'scientific' approaches this modern era.